PERIZINAN TAMBANG GALIAN C DALAM TINJAUAN FIQH AL-BIAH STUDI KASUS DI DESA JOHAR KECAMATAN KARANG BARU - fasya fasya (IAIN Langsa, 2017)
This article tries to address the issue related to environmental demage caused by illegal or legal exploration of natural resource type C in Johar Village. karang baru district. The exploration as such has violated the rule and regulation or the Qanun Kabupaten Aceh Tamiang No. 13. Tahun 2008 that provides legal procedures on the exploration of natural resources type C in the ATam Regency. Not only that the Developer should also look on the matter through environmental fiqh. Both the qanun dan fiqh al biah found that such legal or illegal exploration of the natural resources has caused huge lost only to the region but also the local community in Johar, it demages not only the ecosystem but also deprive the johar people from development.